Controllable Configuration of Sensing Band in a Pressure Sensor by Lenticular Pattern Deformation on Designated Electrodes. Issue 36 (7th July 2019) - Jeong, Chanho; Lee, Ju Seung; Park, Byeonghak; Hong, Chang Seob; Kim, Jong Uk; Kim, Tae‐il
Abstract: Resistive‐type pressure sensor, which are mainly utilized in industry, are easy to manufacture and are not significantly affected by external electromagnetic fields, unlike capacitive type. However, the produce signal is not linear, and it is also difficult to measure a wide range of pressures using such a sensor. Therefore, before being utilized, the extracted nonlinear data from them need to be processed by. A resistive sensor that is capable of measuring a wide range of pressure of up to 4 MPa with constant linearity is presented. Moreover it can selectively control the sensing pressure band, or act as an on/off switch, without the need for any additional computer processing. Abstract : A resistive pressure sensor in which the response characteristic curves can be controlled by a designated electrode is presented. These sensors can perform various functions without additional computing processes, such as on/off switching, low‐pressure band sensing, high‐pressure band sensing, or even linear‐response sensing, over a 4 MPa broad pressure range.